2006
DOI: 10.1128/aac.01042-05
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols Reduce Gastritis Induced by Helicobacter pylori Infection or VacA Toxin Administration in Mice

Abstract: Helicobacter pylori colonizes the human gastric mucosa, causing inflammation that leads to atrophic gastritis, and it can cause peptic ulcer and gastric cancer. We show that polyphenol administration to mice experimentally infected by H. pylori or treated with VacA toxin can limit gastric epithelium damage, an effect that may be linked to VacA inhibition.Helicobacter pylori chronically infects the gastric mucosa of Ͼ50% of the human population, causing gastritis. The infection can lead to the development of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 37 publications
3
28
0
1
Order By: Relevance
“…However, recent scientific data have shown that many plants used as food or in traditional medicine are potentially toxic, mutagenic or carcinogenic (20). In addition, epidemiological data support the idea that tannins, among other vegetal antioxidant agents, have the ability to modulate certain cell signaling pathways and gene expression (21,22). The present study observed the mutagenic potential of P. reticulata bark in order to ensure its safety for human use.…”
Section: Resultsmentioning
confidence: 99%
“…However, recent scientific data have shown that many plants used as food or in traditional medicine are potentially toxic, mutagenic or carcinogenic (20). In addition, epidemiological data support the idea that tannins, among other vegetal antioxidant agents, have the ability to modulate certain cell signaling pathways and gene expression (21,22). The present study observed the mutagenic potential of P. reticulata bark in order to ensure its safety for human use.…”
Section: Resultsmentioning
confidence: 99%
“…Gastritis was graded in antrum, corpus and fundus of each stomach according to the updated Sydney System [18] , and scored from 0 to 3 corresponding to normal, mild, moderate and severe, respectively. Gastric sections were also subjected to immunohistochemical (IHC) staining using either an anti-H pylori polyclonal antibody (HistoLine) or an antiVacA monoclonal antibody as already described [13,19] .…”
Section: Histopathologymentioning
confidence: 99%
“…Plant-derived substances have been reported to limit H pylori gastric colonization in Mongolian gerbils [10,11] . We have previously found that polyphenols and polyphenol-rich beverages, such as tea and wine, inhibit VacA activity in vitro [12] , and that some polyphenols can limit both H pylori-and VacA-induced gastric damage in vivo [13] . Also, it has been recently reported that hop bract extract exerts anti-VacA activity in vitro and in vivo [14] .…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, the antibacterial activity of both herbal extracts and foodstuffs has been associated with their content in phenolic compounds, in particular, flavonoids (11)(12)(13), resveratrol (6), and hydrolyzable tannins (14). The mechanism by which phenolic compounds affect the growth of H. pylori is unknown, but different theories have been proposed, for example, inhibition of the urease activity (15), adhesion to human gastric mucus (10), disintegration of the outer membrane (16), and inhibition of VacA citotoxin activity which causes the development of inflammation and ulceration in patients (17,18).…”
Section: Introductionmentioning
confidence: 99%